2000
DOI: 10.1179/joc.2000.12.6.530
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Transient Hearing Loss Associated with Vincristine Therapy: Case Report

Abstract: Vincristine, adriamycin, and dexamethasone (VAD) chemotherapy protocol is first-choice treatment in newly diagnosed multiple myeloma patients in many centers. Sudden hearing loss associated with vincristine therapy is a rarely observed event in the VAD protocol. We describe a 69-year old male patient diagnosed with multiple myeloma 7 months ago who developed sudden bilateral hearing loss related to vincristine therapy. This uncommon adverse effect of vincristine is discussed and the literature reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…However there are few reports of cases of bilateral sensorineural hearing loss in patients who received high doses of vincristine (2-2.5 mg/m 2 ) [5][6][7]. Experimental studies in rabbits support that vincristine may cause degeneration of hair cells [8].…”
Section: Introductionmentioning
confidence: 92%
“…However there are few reports of cases of bilateral sensorineural hearing loss in patients who received high doses of vincristine (2-2.5 mg/m 2 ) [5][6][7]. Experimental studies in rabbits support that vincristine may cause degeneration of hair cells [8].…”
Section: Introductionmentioning
confidence: 92%
“…Various authors have reported hearing impairment/ deafness due to vincristine therapy [2], plasmacytoma [3] external ear canal mass [4] and inner ear venous thrombosis [5] in myeloma patients. Hearing loss has been reported as a rare side effect of thalidomide used in myeloma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Low and moderate doses of vincristine ( 1.5 mg/m 2 ) do not seem to have any significant harmful effect on pure tone or speech audiometry. However, there are few reports of bilateral sensorineural hearing loss in adult patients who received high doses of vincristine (2-2.5 mg/m 2 ) [3][4][5]. A case of vinblastine-induced tinnitus and mild high-frequency sensorineural hearing loss has also been reported in a patient suffering from Hodgkin's disease [6].…”
Section: Introductionmentioning
confidence: 93%